Physical processing for decellularized nerve xenograft in peripheral nerve regeneration - Hsu, Ming-Wei; Chen, Szu-Han; Tseng, Wan-Ling; Hung, Kuo-Shu; Chung, Tzu-Chun; Lin, Sheng-Che; Koo, Jahyun; Hsueh, Yuan-Yu (Frontiers in Bioengineering and Biotechnology, 2023)
In severe or complex cases of peripheral nerve injuries, autologous nerve grafts are the gold standard yielding promising results, but limited availability and donor site morbidity are some of its disadvantages. Although biological or synthetic substitutes are commonly used, clinical outcomes are inconsistent. Biomimetic alternatives derived from allogenic or xenogenic sources offer an attractive off-the-shelf supply, and the key to successful peripheral nerve regeneration focuses on an effective decellularization process. In addition to chemical and enzymatic decellularization protocols, physical processes might offer identical efficiency. In this comprehensive minireview, we summarize recent advances in the physical methods for decellularized nerve xenograft, focusing on the effects of cellular debris clearance and stability of the native architecture of a xenograft. Furthermore, we compare and summarize the advantages and disadvantages, indicating the future challenges and opportunities in developing multidisciplinary processes for decellularized nerve xenograft.